Food Distribution Policies in the Light of the Qur’anic Directives: An Evaluative Study - Faruk, Mohammad Omar; Hoque, Muhammad Tazammol (Jagannath University Journal of Arts, 2026)
This study examines the Qur’anic principles of food distribution as a foundational framework for ensuring human security, socio-economic justice, and ethical resource management. The Qur’an presents a comprehensive system that emphasizes adequate food production, equitable distribution, and welfare-oriented spending. Through obligatory mechanisms such as zakat, ushr, and sadaqah, Islam establishes the rights of the poor over the wealth of the affluent. In addition, the Qur’anic model strictly prohibits unethical practices such as hoarding, adulteration, fraudulent transactions, and the creation of artificial scarcityÍthat undermine food security. Drawing on classical exegesis, Prophetic traditions, and contemporary scholarly literature, this analytical and evaluative study explores the structural components of Qur’anic food distribution policy. The findings reveal that the Qur’anic framework not only ensures justice and balance in resource allocation but also promotes sustainability and moral accountability, making it highly relevant to current global and national food management challenges. Jagannath University Journal of Arts, v-15, i-2, 2025:p56-75